Effect of Support on the Activity of Ag-based Catalysts for Formaldehyde Oxidation - Zhang, Jianghao (Sci Rep, 2015)
Ag-based catalysts with different supports (TiO(2), Al(2)O(3) and CeO(2)) were prepared by impregnation method and subsequently tested for the catalytic oxidation of formaldehyde (HCHO) at low temperature. The Ag/TiO(2) catalyst showed the distinctive catalytic performance, achieving the complete HCHO conversion at around 95 °C. In contrast, the Ag/Al(2)O(3) and Ag/CeO(2) catalysts displayed much lower activity and the 100% conversion was reached at 110 °C and higher than 125 °C, respectively. The Ag-based catalysts were next characterized by several methods. The characterization results revealed that supports have the dramatic influence on the Ag particle sizes and dispersion. Kinetic tests showed that the Ag based catalyst on the TiO(2), Al(2)O(3) or CeO(2) supports have the similar apparent activation energy of 65 kJ mol(−1), indicating that the catalytic mechanism keep immutability over these three catalysts. Therefore, Ag particle size and dispersion was confirmed to be the main factor affecting the catalytic performance for HCHO oxidation. The Ag/TiO(2) catalyst has the highest Ag dispersion and the smallest Ag particle size, accordingly presenting the best catalytic performance for HCHO oxidation.